Analisis Perbandingan Sistem Pendukung Keputusan Pada Rentang Kelompok Usia Pasien Di Puskesmas Menggunakan Metode Weight Product Dan Topsis - Rizky Ainul Prasetio; Yessi Fitri Annisah Lubis (SNASTIKOM, 2022)
The range of patient age groups is the age category of the population based on their welfare group. Age group aims to look at certain welfare groups that are dominated by relatively productive age groups or dominated by non-productive age groups, for example, children or the elderly. There are several criteria used to calculate the decision support system, namely age range, type of activity, and number category. In this case the researcher wants to design and make a decision support system application using the comparison of the WP method and the topsis method which aims to determine the age group of patients who visit the most health centers. Researchers will conduct research at the Old Village Health Center with the title "Comparative Analysis of Decision Support Systems in the Range of Patient Age Groups in Health Centers Using Weight Product and Topsis Methods".